PEMANFAATAN INTERNET MARKETING MELALUI MEDIA SOSIAL DALAM PEMASARAN UNTUK PELAKU UMKM DI DESA BENER KECAMATAN MAJENANG - Laili Ulviah; Hendro Welas Setiawan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Bener Village is one of the villages in Majenang District. MSMEs in this village experienced a decline in income. They market their products conventionally or open physical stores. To increase their income, they need training to market their products in different ways, such as using internet marketing through social media. The purpose of this service is to provide understanding and training about the use of internet marketing via social media in marketing for MSMEs. The instruments used were questionnaires, laptops, smartphones and LCD projectors. Data was obtained from a questionnaire and then the percentage was calculated. The result of this service is an increase in participants' understanding of internet marketing and an increase in product sales for MSME players.